2004
DOI: 10.1002/bem.10180
|View full text |Cite
|
Sign up to set email alerts
|

Human head exposure to a 37 Hz electromagnetic field: Effects on blood pressure, somatosensory perception, and related parameters

Abstract: Previous studies have shown that exposure to an electromagnetic field (EMF) of 37 Hz at a flux density of 80 microT peak enhances nociceptive sensitivity in mice. Here we examined the effects on pain sensitivity and some indexes of cardiovascular regulation mechanisms in humans by measuring electrical cutaneous thresholds, arterial blood pressure, heart rate and its variability, and stress hormones. Pain and tolerance thresholds remained unchanged after sham exposure but significantly decreased after electroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 29 publications
1
31
2
Order By: Relevance
“…Using a 50 Hz Weld with Xux densities of either 40 or 80 T for 90 min of exposure, Ghione et al (2005) found no eVect on blood pressure or HR. These results were in agreement with their earlier results demonstrating that a 37 Hz, 80 T exposure did not result in alterations of cardiac rhythm (Ghione et al 2004). In a shift of research focus, Sait et al (2006) designed a study that provoked controlled changes in the sympathetic-parasympathetic balance in order to determine if there were any subtle Weld related changes.…”
Section: Laboratory Studiessupporting
confidence: 88%
See 3 more Smart Citations
“…Using a 50 Hz Weld with Xux densities of either 40 or 80 T for 90 min of exposure, Ghione et al (2005) found no eVect on blood pressure or HR. These results were in agreement with their earlier results demonstrating that a 37 Hz, 80 T exposure did not result in alterations of cardiac rhythm (Ghione et al 2004). In a shift of research focus, Sait et al (2006) designed a study that provoked controlled changes in the sympathetic-parasympathetic balance in order to determine if there were any subtle Weld related changes.…”
Section: Laboratory Studiessupporting
confidence: 88%
“…The contrasting results between the two studies ( Table 2) by Ghione et al (2004Ghione et al ( , 2005 might be explained by the drawing of a 20 ml blood sample prior to exposure in the Wrst study, which was not done in the second one. Graham et al have previously reported that physiological arousal associated with blood sampling was likely responsible for the eVects on HRV they observed in some of their studies .…”
Section: Laboratory Studiesmentioning
confidence: 69%
See 2 more Smart Citations
“…In contrast, Ghione and colleagues exposed 10 volunteers for 60 min to a head only, 37-Hz MF at a flux density of 80 lT. They observed a significant increase in systolic blood pressure during MF exposure; however, no HR effects were seen during this same time frame (Ghione et al 2004). In a subsequent study, the same authors examined the effects of head only exposure for 90 min to a 50-Hz field with a flux density of either 40 or 80 lT. No MF exposure effects were observed for HR or blood pressure in either of the exposure groups (Ghione et al 2005).…”
Section: Introductionmentioning
confidence: 86%